Costs of cloud IAAS in businesses - Kučera, Adam; Lorenc, Miroslav, 1974-; Koliš, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
Cloud computing brings many possibilities for businesses, large or small, which they can leverage for reduction of their IT infrastructure costs. This thesis presents the key concepts of cloud computing and its main advantages and disadvantages for enterprises. It compares different cloud IAAS providers and presents a framework for comparison of classic on-premises infrastructure costs and Infrastructure as a Service costs.
Vedoucí práce: Miroslav Lorenc
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses